Balloon dilation in sheath technique in transcatheter aortic valve replacement via narrow femoral artery: first-in-human early feasibility study - Sun, Xiaoqian; Liu, Xiangjuan; An, Luyao; Qie, Liangyi; Ma, Lianyue; Meng, Xiao; Lu, Huixia; Yao, Guihua; Dong, Mei; An, Guipeng (Frontiers in Medicine, 2026)
BackgroundSevere aortic stenosis (AS) imposes sustained pressure overload on the left ventricle, leading to hypertrophy and myocardial fibrosis, which are key features of adverse cardiac remodeling. Timely transcatheter aortic valve replacement (TAVR) may reverse these processes. Transfemoral access remains the primary access method for TAVR, but the limited technique restricts early intervention in patients with narrow femoral arteries. This study aimed to evaluate the safety and feasibility of a novel balloon dilation in sheath (BinS) technique designed to facilitate transfemoral TAVR in such patients.MethodsThis multicenter, prospective, and first-in-human early feasibility study included patients with severe AS and challenging femoral anatomy who underwent TAVR using the BinS technique between February 2023 and August 2024. The primary endpoint was the 30-day rate of major adverse events. The secondary endpoint was the rate of major adverse events at 6 months. The clinical endpoints included major post-procedural complications.ResultsFifteen patients (mean age 73.5 ± 7.3 years; 66.7% male) were treated successfully with the BinS technique via transfemoral access. There were no cases of all-cause mortality, stroke/transient ischemic attack, or severe major vascular access site complications defined by Valve Academic Research Consortium (VARC)-3 at both 30 days and 6 months. No myocardial infarction or paravalvular leakage was observed. 12 patients obtained VARC-3 technical success. Two patients experienced postprocedural arterial dissection, and two developed new-onset conduction abnormalities (left bundle branch block or permanent pacemaker implantation). At 30 days, left ventricular ejection fraction improved significantly from 50.8 ± 17.0% pre-procedure to 59.9 ± 14.6% post-procedure (p < 0.001).ConclusionThe BinS technique appears to be a safe and effective method for enlarging the narrow femoral lumens during TAVR. By broadening transfemoral TAVR eligibility, this approach may permit earlier hemodynamic unloading, thereby mitigating adverse cardiac remodeling and potentially improving long-term outcomes. Larger, longer-term studies are warranted to confirm these findings.